MEASURING STUDENT COGNITIVE LOAD IN CELL BIOLOGY LECTURES - nengsih juanengsih; Adi Rahmat; Ana Ratna Wulan (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
PENGUKURAN BEBAN KOGNITIF MAHASISWA DALAM PERKULIAHAN BIOLOGI SEL AbstractThis research is a descriptive study that aims to obtain a picture of the cognitive load of biology students on cell biology lecture. The study was conducted at the Biology Education Study Program in one of the Universities in Jakarta. Data collection was carried out in the even semester of the 2015/2016 academic year, in October 2015. The subject was 55 students who enrolled in cell biology courses was 55 students. Intrinsic cognitive load (ICL) is described in reverse through the ability to process information that is measured by using instrument that contain questions related to information received in the lecture in the form of student worksheets. Extraneous cognitive load (ECL) is described and measured by using a subjective rating scale questionnaire based on a Likert scale, contain statements about students' efforts in understanding the information received in the lecture. Germane cognitive load (GCL) is described and measured through unit tests conducted at the end of the lecture in the form of essay tests. The relationship between the three components of cognitive load was analyzed through correlation tests. The results showed the average student information processing ability was 91.12 (low ICL) with a mean mental effort of 61.31 (high ECL). For average learning outcomes 37.39 (low GCL). The results of statistical tests, it is known that the correlation of the information processing ability with mental effort inversely proportional (negative correlation) which shows students' information processing ability can help reduce mental effort in cell biology lectures. The high ECL and low GCL have implications for the need to improve cell biology learning strategies to reduce the students’s cognitive load.AbstrakPenelitian ini merupakan penelitian deskriptif yang bertujuan untuk memperoleh gambaran beban kognitif mahasiswa biologi pada perkuliahan biologi sel. Penelitian dilaksanakan di Prodi Pendidikan Biologi di salah satu Perguruan Tinggi di Jakarta. Pengambilan data dilaksanakan pada semester genap tahun akademik 2015/2016, bulan Oktober 2015. Subjek penelitian sebanyak 55 orang mahasiswa yang mengontrak mata kuliah biologi sel. Intrinsic cognitive load (ICL) digambarkan secara terbalik melalui kemampuan memproses informasi yang diukur dengan menggunakan instrumen yang yang berisi pertanyaan-pertanyaan terkait informasi yang diterima dalam perkuliahan yaitu berupa lembar kerja mahasiswa (LKM). Extraneous cognitive load (ECL) digambarkan dan diukur dengan menggunakan angket subjective rating scale berbasis skala Likert. Germane cognitive load (GCL) digambarkan dan diukur melalui tes unit yang dilakukan pada akhir perkuliahan berupa soal uraian. Hubungan antara ketiga komponen beban kognitif dianalisis melalui uji korelasi. Hasil penelitian menunjukkan rerata kemampuan memproses informasi mahasiswa sebesar 91,12 (ICL rendah) dengan nilai rerata usaha mentalnya sebesar 61,31 (ECL tinggi). Untuk rerata hasil belajar 37,39 (GCL rendah). Dari hasil uji statistik diketahui korelasi kemampuan memproses informasi dengan usaha mental berbanding terbalik (korelasi negatif) yang menunjukkan kemampuan memproses informasi mahasiswa dapat membantu mengurangi usaha mental dalam perkuliahan biologi sel. Tingginya ECL dan rendahnya GCL memberikan implikasi terhadap perlunya perbaikan strategi pembelajaran biologi sel untuk menurunkan beban kognitif mahasiswa.